2019
DOI: 10.1123/ijspp.2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Versus High-Intensity Multimodal Training in Recreational Runners

Abstract: Recreational runners achieved similar improvement in 5-km performance and body composition through polarized training or CFE, but POL yielded a greater increase in VO max. Extrapolation to longer distances requires additional research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Evidence of CF training being more advantageous towards developing a variety of fitness outcomes in comparison to alternative training strategies (e.g., resistance training, high-intensity interval training) is equivocal [19][20][21][22][23][24][25]. This is likely because most comparative training studies have utilized untrained or novice (to CF) participants, which is problematic because they do not require a very specific or intense training stimulus to elicit adaptations compared to experienced trainees [26].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of CF training being more advantageous towards developing a variety of fitness outcomes in comparison to alternative training strategies (e.g., resistance training, high-intensity interval training) is equivocal [19][20][21][22][23][24][25]. This is likely because most comparative training studies have utilized untrained or novice (to CF) participants, which is problematic because they do not require a very specific or intense training stimulus to elicit adaptations compared to experienced trainees [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Carnes and Mahoney [24] compared the effects of a multimodal training program that combined interval training with HIFT sessions to a polarized endurance training program on maximal oxygen consumption (VO 2max ) and 5-km performance in a group of recreational runners. Over 12 weeks, the multimodal group performed short (30–60 s) and long intervals (1.5–6 min) at the participants’ maximal sustainable effort, in addition to HIFT sessions consisting of a strength activity followed by an intense circuit, while the polarized training group followed a traditional running program.…”
Section: Hift and Metabolic Adaptations For Sport Performancementioning
confidence: 99%
“…Over 12 weeks, the multimodal group performed short (30–60 s) and long intervals (1.5–6 min) at the participants’ maximal sustainable effort, in addition to HIFT sessions consisting of a strength activity followed by an intense circuit, while the polarized training group followed a traditional running program. While the improvements in the VO 2max were greater for the polarized group (4.3 ± 3.6 vs. 1.78 ± 1.9 mL·kg·min −1 ), performance in the 5-km time-trial improved to the same extent in both groups, leading the authors to conclude that recreational runners can obtain a similar degree of improvement in the distance using either approach [24]. In addition, the multimodal training group had a lower running volume during the intervention, highlighting the potential that HIFT has as a time-efficient training strategy.…”
Section: Hift and Metabolic Adaptations For Sport Performancementioning
confidence: 99%
See 1 more Smart Citation
“…A study from Muñoz et al (2014) suggested that PET training can stimulate greater training effects compared with a programme at threshold range intensities in male recreational runners. PET has also shown benefits in raising VO2max compared to cross-fit endurance training in female runners (Carnes & Mahoney, 2019). A recent systematic review of middle-and long-distance runners compared PET to pyramidal training and threshold training (Kenneally, Casado, & Santos-Concejero, 2018).…”
Section: Introductionmentioning
confidence: 99%